2022
DOI: 10.3389/fneur.2021.793663
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis Reveals a 20-Year Research Trend for Chemotherapy-Induced Peripheral Neuropathy

Abstract: ObjectiveA lot of research has focused on the field of chemotherapy-induced peripheral neuropathy (CIPN). In this study, we performed a bibliometric analysis of CIPN-related publications to identify the key research areas and trends over the last 20 years.MethodsWe searched the Web of Science core collection for publications related to CIPN that were published between January 2001 and September 2021. We then performed bibliometric analysis and visualization using Microsoft Excel 2019, VOSviewer, and the Biblio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This dearth of high-quality and consistent evidence was also noted in recent clinical practice guidelines, which-as noted above-only support duloxetine as moderately effective for treatment of existing CIPN (Hershman et al, 2014). More recently, Gu et al reported a 20-year bibliometric analysis highlighting the rise in efforts to study non-pharmacological interventions for CIPN reaching a high point in only the last few years (Gu et al, 2022). Of note, some of the key potential mechanisms underpinning CIPN, including inflammation, may be influenced by exercise, providing a possible mechanistic link (Chung et al, 2022).…”
Section: Non-pharmacological Approachesmentioning
confidence: 90%
“…This dearth of high-quality and consistent evidence was also noted in recent clinical practice guidelines, which-as noted above-only support duloxetine as moderately effective for treatment of existing CIPN (Hershman et al, 2014). More recently, Gu et al reported a 20-year bibliometric analysis highlighting the rise in efforts to study non-pharmacological interventions for CIPN reaching a high point in only the last few years (Gu et al, 2022). Of note, some of the key potential mechanisms underpinning CIPN, including inflammation, may be influenced by exercise, providing a possible mechanistic link (Chung et al, 2022).…”
Section: Non-pharmacological Approachesmentioning
confidence: 90%
“…Chemotherapeutic agents such as taxanes, platinum drugs and Changchun ower alkaloids breast cancer can be neurotoxic [71][72][73]. A study reported that three months after taxane treatment, breast cancer survivors still had chemotherapy-induced peripheral neuropathy [74].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…It has been suggested that separate anatomical pathways exist for these respective components ( 26 , 43 ), the so-called lateral and medial pain system ( 44 ). A schematic presentation of the medial and lateral and medial pain ascending pathways in chemotherapy-induced peripheral neurotoxicity is reported in Figure 2 (evidence is presented in the following citations: 34 , 39 , 43 50 ). Since non-peptidergic fibers are overrepresented in the epidermis, and since the degeneration of these fibers seems to be associated with the affective component of neuropathic pain, it is recommended to use a numerical rating scale (NRS) for pain unpleasantness in addition to an NRS for pain intensity for patients with CIPN-associated neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%